Efficacy and safety of bisphosphonates in management of low bone density in inflammatory bowel disease: A meta-analysis. Issue 3 (January 2017) - Yao, Liwei; Wang, Haiqing; Dong, Wenwei; Liu, Zhenxin; Mao, Haijiao
Abstract : Abstract: This study aims to determine whether bisphosphonates are safe, as well as effective against bone mineral loss in inflammatory bowel disease (IBD). A computerized search of electronic databases from 1966 to 2016 was performed. Randomized controlled trials (RCTs) were included in this review to evaluate the role of bisphosphonates in the management of osteoporosis in IBD patients. A revised 7-point Jadad scale was used to evaluate the quality of each study. Overall, 13 RCTs and 923 patients met the inclusion criteria of this meta-analysis. The result showed that bisphosphonates decreased bone mass density (BMD) loss at the lumbar spine ( P  = 0.0002), reduced the risk of new fractures ( P  = 0.01), and retained the similar adverse events ( P  = 0.86). Bisphosphonates may provide protection and safety against bone mineral loss in IBD patients.